Effect of Various Carboxylic Acids on the Biosynthesis of Polyhydroxyalkanoate in Pseudomonas aeruginosaPA01: Biosynthesis of polyhydroxyalkanoate in Pseudomonas aeruginosa - Kambiz Akbari Noghabi,; Hossein Shahbani Zahiri,; Abbas Sahebghadam Lotfi,; Mitra Shourian,; Gholamreza Karbalaei,; Iman Rad,; Solmaz Ahadi,; Mahmood Arabnezhad, (Iranian Journal of Pharmaceutical Sciences, 2008)
In the present study, four carbon sources were tested for the polyester synthesis of Pseudomonas aeruginosaPA01 which is a ubiquitous environmental bacterium and is one of the top three causes of opportunistic human infections. These included linear C8to C11carboxylic acids. Octanoic acid, nonanoic acid, decanoic acid and undecanoic acid were added to M1 minimal medium to final concentrations of 60,40, 30 and 20 mM, respectively. When P. aeruginosa was cultivated in M1 minimal medium with decanoate and nonanoate as the sole carbon sources, polyhydroxyalka-noate (PHA) was achieved up to 55.75% (w/w) and 24.53% (w/w), respectively. The maximum PHAyield at 30 ºC was obtained when decanoic acid was used as sole carbon source. Use of nonanoic acid as carbon source was resulted in a minimum PHAyield at 30 ºC. An increase in the cultivation temperature from 30 ºC to 37 ºCresulted in decrease of PHAcontent and cell dried weight as well. Based on the type of carbon source different monomers at the level higher than 1 mol% to 62 mol%were detected which included 3-hydroxyoheptanoic acid (C7), 3-hydroxyoctanoicacid (C8), 3-hydroxynonanoic acid (C9), 3-hydroxydecanoic acid (C10), and 3-hydroxyundecanoic acid (C11).